What color is your parachute? : a practical manual for job-hunters and career-changers - Bolles, Richard Nelson (Berkeley : Ten Speed Press, 2015)
Explains how to identify personal goals and interests and reveals how to apply that information toward obtaining satisfying employment, with tips on interviews, salary-negotiation techniques, and career searching online.
Includes bibliographical references and index.
Keywords: Applications for positions; Vocational guidance; Career changes; Job hunting; Applications for positions; Vocational guidance; Career changes; Job hunting